Seroprevalence of Brucellosis from the city Mosul Iraq - I Daood, Ismail; Zajmi, Asdren; Husaien Al Jubory, Ibtihal (International Journal of Psychosocial Rehabilitation, 2020)
Background Brucellosis is a common neglected zoonotic disease transmitted from an animal reservoir to humans. Both wildlife and domestic animals contribute to the spreading of disease, and it is endemic in most Middle Eastern countries, including Iraq. Thus, brucellosis has negatively impacted the economy as well as livestock and health sectors. Aim: The aim of this study was to provide data on the seroprevalence of brucellosis, investigate the status and prevalence among gender and age groups, and evaluate and compare the level of immunoglobulin classes IgG and IgM among the patients with brucellosis symptoms. Methods: A prospective cohort study was conducted among patients with brucellosis symptoms from July 2017 to June 2019 in the city of Mosul in northern Iraq. Blood samples were collected randomly and aseptically from patients with brucellosis symptoms at Mosul General Hospital. The Rose Bengal test (RBT) was used to measure the level of immunoglobulin classes IgG and IgM, as well as an enzyme-linked immunosorbent assay (ELISA) for sensitivity and specificity against brucellosis. Results: A total of 385 sera individuals suffering with clinical features suggestive of Brucellosis who had positives for the RBT test appeared; 115 (29.9%) showed positive reactions in RBT. The study recorded the highest seroprevalence of 28 (38.9%) in females and 16 (23.1%) in males in 2017. But the highest 35 (34.6%) in females and 19 (26% in males) in 2018. The highest seroprevalence was 7 (16.2%) in females and 3 (11.2%) in males in 2019. The study showed a higher seroprevalence of 35 (34.3%) was observed among the age group of (31- 40) years, then 34 (29.1%), 28 (28.2%), and 15 (26.8%) among the age > 40, (21-30) and (11-20) years, respectively. The study record from 30 serum positives by RBT appeared to be 17 (56.6%) positive by ELISA; estimated sensitivity and specificity of the ELISA were RBT 69% and 59%, respectively. Conclusion: In conclusion, the frequency of brucella complications varied between different genders and age groups in the city of Mosul, Iraq. Hence, systemic monitoring as well as education of the population are necessary to prevent the (re)emergence of brucellosis and its complications.